Stimulation of Youth Interest in Agribusiness for Employability - Aruleba, Tomisin James (SEDME (Small Enterprises Development, Management & Extension Journal), 2024)
Despite the great potential of agribusiness that can lead to job creation employment and economic prosperity, the majority of the youths seem to have jettison the economic opportunities. Specifically, the study objectives are to ascertain the components that motivate Nigerian youths to set out into agribusiness in rural communities, examine the challenges of Nigerian youths' employability skills in agribusiness of the rural communities in southwest Nigeria, and assess the mechanisms to confront the challenges being faced by Nigerian youths' employability skills in agribusiness of the rural communities in southwest Nigeria. The study adopted a descriptive survey design. A questionnaire was used to collect adequate data from the target respondents (youths in agribusiness), with a sample size of 100. Multi-stage sampling technique was adopted to sample the rural communities and the respondents. The study reveals that the inability to get a job pushed youths into agribusiness (71 per cent); lack of insurance policy towards agribusiness (88 per cent) and regular training towards incubation purposes is good leverage for youth employability (78 per cent). It, therefore, recommends that relevant stakeholders should further make agribusiness more lucrative by coming up with policies that will entice youths to venture into agribusiness. Also, relevant stakeholders should work towards the complete eradication of the impediments.
Keywords: Agribusiness; Agriculture; Employability; Entrepreneurial; Youth